Studies of firm capital structure determinants in Poland: An integrative review - Andrzej Cwynar; Wiktor Cwynar; Robert Dankiewicz (e-Finanse: Financial Internet Quarterly, 2015)
We investigated 34 empirical studies aimed at examining the capital structure determinants in firms operating in Poland to test to what degree the financing patterns were steady during the observed period (2001-2012). Specifically, in conducting the survey we were motivated by the following research questions which constitute the objectives of the article: (1) which factors - country- or firm-specific - are more relevant in explaining leverage in Poland, (2) which theory - trade-off or pecking order - gains greater support in Poland, and (3) what is the significance of the optimal capital structure notion in Poland. Our results show that financing patterns changed importantly during the last 20 years, which manifests itself mainly in gradual increase in debt ratios with a dominant role of short-term debt, along with the decrease in the importance of country-specific factors (especially in large-sized, listed firms). The signs of the associations between leverage and the key firm-specific factors remained relatively stable during the investigated period, with the exception concerning tangibility. These signs provide greater support for pecking order theory, with at most a moderate role of the target capital structure.
Keywords: G32; 330; capital structure; equity; debt; leverage; financing